2012
DOI: 10.1371/journal.pone.0031515
|View full text |Cite
|
Sign up to set email alerts
|

PKC Theta Ablation Improves Healing in a Mouse Model of Muscular Dystrophy

Abstract: Inflammation is a key pathological characteristic of dystrophic muscle lesion formation, limiting muscle regeneration and resulting in fibrotic and fatty tissue replacement of muscle, which exacerbates the wasting process in dystrophic muscles. Limiting immune response is thus one of the therapeutic options to improve healing, as well as to improve the efficacy of gene- or cell-mediated strategies to restore dystrophin expression. Protein kinase C θ (PKCθ) is a member of the PKCs family highly expressed in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…Taken together with the work of Oh and collaborators, demonstrating that slow fiber expression during embryogenesis and early postnatal growth is under the control of a developmental program in a calcineurin-independent manner (Oh et al, 2005), we investigated the expression level of another calcium-dependent protein, PKCα. In accordance with previously published data that demonstrated that PKCα exerted a primary role in pathogenesis of DMD (Wang et al, 2009;Madaro et al, 2012), we showed its early overactivation in DMD fetal muscle tissues. PKCα is involved in signal transduction cascades regulating the proliferation of myoblasts (Goel and Dey, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together with the work of Oh and collaborators, demonstrating that slow fiber expression during embryogenesis and early postnatal growth is under the control of a developmental program in a calcineurin-independent manner (Oh et al, 2005), we investigated the expression level of another calcium-dependent protein, PKCα. In accordance with previously published data that demonstrated that PKCα exerted a primary role in pathogenesis of DMD (Wang et al, 2009;Madaro et al, 2012), we showed its early overactivation in DMD fetal muscle tissues. PKCα is involved in signal transduction cascades regulating the proliferation of myoblasts (Goel and Dey, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…(2009), Madaro et al (2012) and the work of Kawasaki, demonstrating the role of PKC in the phosphorylation of Orai1 (Kawasaki et al, 2010), we decided to investigate the expression of PKCα in murine fetal muscle tissues. In skeletal muscle, PKCα Development (2016Development ( ) 143, 658-669 doi:10.1242 protein is regulated by Ca 2+ concentration and plays a fundamental role in muscle development and plasticity (Gundersen, 2011).…”
Section: Expression Of Ca 2+ Channels In Murine Fetal Muscle Tissuesmentioning
confidence: 99%
“…In this study, we examined the acute inflammatory cell infiltrate in 2-, 4-, and 12-week-old mdx muscle, and determined the kinetics of T-cell infiltration, thus identifying the relevant period for T-cell-based interventions. To target T cells, we used the compound C20, a potent and selective protein kinase C theta (PKCθ) inhibitor [25][26][27][28][29][30][31][32]. PKCθ is a key regulator of effector T-cell activation [26,[33][34][35] and previous studies have shown that lack of PKCθ ameliorates T-cell-mediated inflammatory diseases [34,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Madaro et al in 2012 [36] showed that in double null mice pkcθ/mdx the muscle wasting was significantly reduced, while muscle regeneration was increased with respect to mdx dystrophic mice. This response was mainly associated with the lack of PKCθ in inflammatory cells, suggesting that PKCθ could represent a pharmacological target to improve the efficacy of therapy approach [37].…”
Section: Pkcs and Muscular Dystrophiesmentioning
confidence: 99%